Adamantinomatous craniopharyngiomas express tumor stem cell markers in cells with activated Wnt signaling: further evidence for the existence of a tumor stem cell niche? - Hölsken, Annett; Stache, Christina; Schlaffer, Sven-Martin; Flitsch, Joerg; Fahlbusch, Rudolf; Buchfelder, Michael; Buslei, Rolf (Pituitary, 2014)
Early disease onset, clinical manifestation, histomorphology, and increased tendency to relapse distinguish the adamantinomatous craniopharyngioma (adaCP) from the more favorable papillary variant (papCP). A molecular hallmark of adaCP is the activated Wnt signaling pathway indicated by nuclear ?-catenin accumulation in a subset of tumor cells. A mouse model recently illustrated that these cells are the driving force in tumorigenesis of adaCP. This observation and the peculiar growth pattern points to the existence of a specific tumor stem cell (TSC) population in human CP.To prove this hypothesis, the TSC markers CD133 (Prominin1) and CD44 were examined in papCP (n = 8) and adaCP (n = 25) on mRNA level using quantitative real time PCR of total tumor RNA. Furthermore, we investigated protein expression performing immunohistochemical analyses of formalin-fixed paraffin embedded tumor samples.PapCP revealed a homogenous CD44 expression pattern predominantly at the cell membrane, whereas CD133 labeling was hardly detectable. In adaCP, on the other hand all markers were consistently and predominantly co-expressed in nuclear ?-catenin accumulating cell clusters, which was confirmed by double immunofluorescence staining. Overall expression of CD44 was significantly decreased in adaCP versus papCP, whereas CD133 showed significantly higher protein and mRNA levels in adaCP.Our results indicate tumor stem cell-like characteristics of ?-catenin accumulating cell clusters in adaCP, which may represent a tumor stem cell niche and might contribute to tumor recurrence. The potential impact of these special cell groups in regard to future CP management, including postoperative follow-up and additional treatment remains to be explored.
EVALuna2:7205

Drug priming enhances radiosensitivity of adamantinomatous craniopharyngioma via downregulation of survivin - Stache, Christina; Bils, Christiane; Fahlbusch, Rudolf; Flitsch, Joerg; Buchfelder, Michael; Stefanits, Harald; Czech, Thomas; Gaipl, Udo; Frey, Benjamin; Buslei, Rolf; Hoelsken, Annett (Neurosurgical Focus, 2016)
OBJECTIVE In this study, the authors investigated the underlying mechanisms responsible for high tumor recurrence rates of adamantinomatous craniopharyngioma (ACP) after radiotherapy and developed new targeted treatment protocols to minimize recurrence. ACPs are characterized by the activation of the receptor tyrosine kinase epidermal growth factor receptor (EGFR), known to mediate radioresistance in various tumor entities. The impact of tyrosine kinase inhibitors (TKIs) gefitinib or CUDC-101 on radiation-induced cell death and associated regulation of survivin gene expression was evaluated. METHODS The hypothesis that activated EGFR promotes radioresistance in ACP was investigated in vitro using human primary cell cultures of ACP (n = 10). The effects of radiation (12 Gy) and combined radiochemotherapy on radiosensitivity were assessed via cell death analysis using flow cytometry. Changes in target gene expression were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Survivin, identified in qRT-PCR to be involved in radioresistance of ACP, was manipulated by small interfering RNA (siRNA), followed by proliferation and vitality assays to further clarify its role in ACP biology. Immunohistochemically, survivin expression was assessed in patient tumors used for primary cell cultures. RESULTS In primary human ACP cultures, activation of EGFR resulted in significantly reduced cell death levels after radiotherapy. Treatment with TKIs alone and in combination with radiotherapy increased cell death response remarkably, assessed by flow cytometry. CUDC-101 was significantly more effective than gefitinib. The authors identified regulation of survivin expression after therapeutic intervention as the underlying molecular mechanism of radioresistance in ACP. EGFR activation promoting ACP cell survival and proliferation in vitro is consistent with enhanced survivin gene expression shown by qRT-PCR. TKI treatment, as well as the combination with radiotherapy, reduced survivin levels in vitro. Accordingly, ACP showed reduced cell viability and proliferation after survivin downregulation by siRNA. CONCLUSIONS These results indicate an impact of EGFR signaling on radioresistance in ACP. Inhibition of EGFR activity by means of TKI treatment acts as a radiosensitizer on ACP tumor cells, leading to increased cell death. Additionally, the results emphasize the antiapoptotic and pro-proliferative role of survivin in ACP biology and its regulation by EGFR signaling. The suppression of survivin by treatment with TKI and combined radiotherapy represents a new promising treatment strategy that will be further assessed in in vivo models of ACP.
EVALuna2:7353

Insights into the infiltrative behavior of adamantinomatous craniopharyngioma in a new xenotransplant mouse model - Stache, Christina; Hoelsken, Annett; Schlaffer, Sven-Martin; Heß, Andreas; Metzler, Markus; Frey, Benjamin; Fahlbusch, Rudolf; Flitsch, Joerg; Buchfelder, Michael; Buslei, Rolf (Brain Pathology, 2015)
Adamantinomatous craniopharyngiomas (adaCP) cause hypothalamic pituitary dysfunction. Elucidation of pathomechanisms underlying tumor progression is essential for the development of targeted chemotherapeutic treatment options. In order to study the mechanisms of tumor outgrowth, we implanted human primary adaCP tissue from three different surgical specimens stereotactically into the brain of immunodeficient mice (n = 20). Three months after tumor inoculation, magnetic resonance imaging and histology confirmed tumor engraftment in all 20 mice (100%) that obtained tissue transplants. The lesions invaded adjoining brain tissue with micro finger-shaped protrusions. Immunohistochemical comparison of the primary tumor and xenotransplants revealed a similar amount of proliferation (Mib-1) and cytokeratin expression pattern (KL-1). Whole tumor reconstruction using serial sections confirmed whirl-like cell clusters with nuclear ?-catenin accumulations at the tumor brain border. These whirls were surrounded by a belt of Claudin-1 expressing cells, showed an activated epidermal growth factor receptor (EGFR) and distinct CD133 as well as p21(WAF1/Cip1) positivity, indicating a tumor stem cell phenotype. Consistent with our previous in vitro studies, intracranial xenotransplants of adaCP confirmed cells with nuclear ?-catenin and activated EGFR being the driving force of tumor outgrowth. This model provides the possibility to study in vivo tumor cell migration and to test novel treatment regimens targeting this tumor stem cell niche.
EVALuna2:7210

Novel technique for high-precision stereotactic irradiation of mouse brains - Hartmann, Josefin; Wölfelschneider, Jens; Stache, Christina; Buslei, R.; Derer, Anja; Schwarz, Martin; Bäuerle, Tobias; Fietkau, Rainer; Gaipl, Udo; Bert, Christoph; Hoelsken, A.; Frey, Benjamin (Strahlentherapie und Onkologie, 2016)
Small animal irradiation systems were developed for preclinical evaluation of tumor therapy closely resembling the clinical situation. Mostly only clinical LINACs are available, so protocols for small animal partial body irradiation using a conventional clinical system are essential. This study defines a protocol for conformal brain tumor irradiations in mice.CT and MRI images were used to demarcate the target volume and organs at risk. Three 6 MV photon beams were planned for a total dose of 10 fractions of 1.8 Gy. The mouse position in a dedicated applicator was verified by an X-ray patient positioning system before each irradiation. Dosimetric verifications (using ionization chambers and films) were performed. Irradiation-induced DNA damage was analyzed to verify the treatment effects on the cellular level.The defined treatment protocol and the applied fractionation scheme were feasible. The in-house developed applicator was suitable for individual positioning at submillimeter accuracy of anesthetized mice during irradiation, altogether performed in less than 10 min. All mice tolerated the treatment well. Measured dose values perfectly matched the nominal values from treatment planning. Cellular response was restricted to the target volume.Clinical LINAC-based irradiations of mice offer the potential to treat orthotopic tumors conformably. Especially with respect to lateral penumbra, dedicated small animal irradiation systems exceed the clinical LINAC solution.
EVALuna2:7317

Tight junction protein claudin-1 is differentially expressed in craniopharyngioma subtypes and indicates invasive tumor growth - Stache, Christina; Hölsken, Annett; Fahlbusch, Rudolf; Flitsch, Jörg; Schlaffer, Sven-Martin; Buchfelder, Michael; Buslei, Rolf (Neuro-Oncology, 2014)
Background Claudins are tight junction proteins expressed in epithelial tissues that play important roles in cell polarity and adhesion. Altered distribution of claudin-1(CLDN1) affects cell mobility and tumor invasiveness. Craniopharyngiomas (CPs) represent epithelial tumors of the sellar region, consisting of adamantinomatous (adaCP) and papillary (papCP) variants. Their tendency to infiltrate surrounding brain structures complicates successful surgery. Reliable markers are required to predict tumor behavior and to establish individualized treatment protocols. Methods We describe the distribution pattern of CLDN1 in a large cohort of 66 adaCPs, 21 papCPs, and 24 Rathke`s cleft cyst (RCC) cases using immunohistochemistry. CLDN1 mRNA levels were analyzed with qRT-PCR in 33 CP samples. The impact on the migration potential was studied in primary adaCP cell cultures (n = 11) treated with small interfering RNA (siRNA) for CLDN1. Furthermore, CLDN1 distribution patterns and expression levels were compared between invasive (n = 16) and noninvasive (n = 17) tumor groups. Results PapCPs and RCCs exhibited a distinct homogenous and membranous expression pattern, whereas CLDN1 immunoreactivity appeared weaker and more heterogeneous in adaCPs. In the latter cases, whirl-like cell clusters showed complete absence of CLDN1. mRNA analysis confirmed reduced CLDN1 levels in adaCPs versus papCPs. Interestingly, invasive tumors exhibited significantly lower CLDN1 expression compared with noninvasive counterparts regardless of CP subtype. Accordingly, siRNA treatment for CLDN1 altered tumor cell migration in vitro. Conclusion CLDN1 represents a novel marker in the differential diagnosis of CP variants and RCCs. Low CLDN1 expression levels correlate with an invasive CP growth pattern and may serve as a prognostic marker.
EVALuna2:7206